Need Support in Students with Visual Impairments: Comparing Teacher and Student Perspectives - Haakma, Ineke; Janssen, Marleen J.; Minnaert, Alexander E. M. G. (Frontiers in Education, 2018)
According to Self-Determination Theory, need-supportive teaching positively influences students’ engagement to learn. Need-supportive teaching involves teachers providing students with structure, autonomy support, and involvement. It enables teachers to support students’ psychological needs to feel competent, autonomous, and related. Supporting students’ needs consequently has a positive influence on students’ engagement to learn. Little is known about need-supportive teaching in the education of students with visual impairments. In this study we used a questionnaire to assess the self-reported provision of need support by teachers of students with visual impairments, the students’ perceived need support and the students’ behavioral and emotional engagement. Seven teachers and forty-eight students filled in questionnaires based on Self-Determination Theory. In general, mean scores were positive. The teachers’ mean scores for the need support they provided, the students’ mean scores for their perceived need support, and the students’ mean scores for engagement all ranged between 3 and 4 on a 5-point scale. The teachers and students scored highest on involvement, followed by structure, and then autonomy support. When looking at scores on an individual student level, we found large differences between students in the same class, which implies that need support requires an individualized approach. Hence, teachers need to be aware of their students’ individual needs for structure, autonomy support, and involvement and should adjust their need-supportive teaching accordingly, thereby enabling teachers to have a positive impact on the engagement of students with visual impairments.